Power transmission (Transmission system operation)
The main objective of this module, is to draw attention to the major features of transmission system equipment, and operation of transmission lines. Particular attention is paid to limitations resulting from the effects of resistance, inductance, and capacitance of the lines. Topics include construction features of overhead and underground transmission, application of HVDC transmission, transmission lines properties and resultant losses, line voltage drop and power angle, effect of line capacitance and charging current, substation layout, line voltage compensating equipment and transformer construction.